Determinant of Mudharabah Financing: A Study at Indonesian Islamic Rural Banking - Erika Amelia; Eva Fauziah Hardini (Faculty of Economic and Business, 2017)
This study aims to determine the variables that affect the financing in the Islamic rural banking in Indonesia. The data used in this study is a monthly time series data that is from June 2009 until June 2015 in the monthly financial statements Islamic Banking Statistics published by Bank Indonesia. The analytical method used in this research is multiple linear regressions. The results of data analysis showed that the variables simultaneously deposit fund, capital adequacy ratio, inflation, exchange rate and the level of revenue sharing significantly influence the composition of financing. Partially deposit funds and the exchange rate significant positive effect, while capital adequacy ratio had a negative effect. Variable inflation and the level of revenue sharing do not significantly influence the composition of financing. This result implies that Islamic rural banking should increase the deposit funds to increase the mudaraba financing.DOI: 10.15408/etk.v16i1.4638